Analysis of the balance between U.S. monetary and fiscal policy using simulated wavelet-based optimal tracking control - Patrick M. Crowley; David Hudgins (Bank of Finland, 2016)
This paper uses wavelet-based optimal control to simulate fiscal and monetary strategies under different levels of policy restrictions. The model applies the Maximal Overlap Discrete Wavelet Transform (MODWT) to United States quarterly GDP data, and then uses the decomposed variables to build a large 80 dimensional state-space linear-quadratic tracking model. Using a political targeting design for the frequency range weights, we simulate jointly optimal fiscal and monetary policy where: (1) both fiscal and monetary policy are dually emphasized, (2) fiscal policy is unrestricted while monetary policy is restricted to achieving a steady increase in the market interest rate, and (3) only monetary policy is relatively active, while fiscal spending is restricted to achieving a target growth rate. The results show that fiscal policy must be more aggressive when the monetary authorities are not accommodating the fiscal expansion, and that the dual-emphasis policy leads a series of interest rate increases that are balanced between a steadily increasing target and a low, fixed rate. This research is the first to construct integrated fiscal and monetary policies in an applied wavelet-based optimal control setting using U.S. data.
URN:NBN:fi:bof-201608121371
Keywords: C49; C61; C63; C88; E58; E61; 330